ANALYSIS OF GENETIC VARIATION MUTANT SOYBEAN (Glycine max. L.MERR) GAMMA RAYS AND EMS (ETHYL METHANE SULFONATE) INDUCTION THROUGH ISSR MOLECULAR MARKERS - Evika Sandi Savitri (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Mutation induction in soybeans was carried out to develop high genetic diversity as a basis for plant breeding to get superior varieties. Mutation induction can be done using physically mutagen gamma rays and chemically using EMS mutagens. This study aims to determine the effectiveness of chemical mutagen (EMS) and physical mutagen (gamma rays) in the induction of genetic diversity in soybeans. Mutation detection can be done with molecular markers to characterize plant genetic diversity. In this study, ISSR molecular markers were used consisting of 4 primers. The method of mutation induction used EMS and gamma rays treatment. The results of the primary PCR amplification of ISSR2, ISSR3 and UBC888 showed 100% polymorphism. The treatment of mutation induction using EMS chemical agents showed a higher degree of polymorphism compared to gamma rays treatment